The effect of Truth or Dare wordwall media on increasing students' self-confidence - Nadia Izza Shabrina; Arum Fatayan (Curricula: Journal of Curriculum Development, 2025)
Conventional teaching methods often fail to foster emotional engagement among students, thereby limiting active participation and the development of self-confidence, particularly in Pancasila and Citizenship Education (PPKn). Alongside this, the rise of digital technology has significantly influenced elementary education, including the adoption of interactive tools such as Wordwall, as implemented at SDN Balimester 06 Pagi, East Jakarta. This study aims to evaluate the effect of Wordwall-based Truth or Dare card media on enhancing the self-confidence of fifth-grade students in PPKn learning. A quasi-experimental design with a pre-test and post-test control-group model was employed, involving 60 students, equally divided into experimental and control groups. The experimental group utilized the Wordwall-based Truth or Dare media, while the control group continued with conventional learning methods. The findings revealed a significant improvement in students’ self-confidence within the experimental group, as reflected in their increased activeness, willingness to express opinions, and participation in class discussions. These results indicate that interactive digital media such as Wordwall can serve as an innovative learning strategy to create an engaging and enjoyable classroom atmosphere.   Abstrak Metode pengajaran konvensional sering kali kurang mampu membangun keterlibatan emosional murid sehingga menghambat partisipasi aktif dan perkembangan kepercayaan diri murid, khususnya pada mata pelajaran Pendidikan Pancasila dan Kewarganegaraan (PPKn). Selain itu, perkembangan teknologi digital telah membawa perubahan signifikan dalam praktik pendidikan di sekolah dasar, salah satunya dengan adanya penggunaan media wordwall seperti yang terjadi di SDN Balimester 06 Pagi, Jakarta Timur. Penelitian ini bertujuan untuk mengevaluasi pengaruh media kartu Truth or Dare berbasis Wordwall terhadap peningkatan sikap percaya diri murid kelas V dalam pembelajaran PPKn. Penelitian ini menggunakan desain kuasi-eksperimen dengan model pre-test dan post-test control group, melibatkan 60 murid yang dibagi dalam kelompok eksperimen dan kontrol. Kelompok eksperimen menggunakan media Truth or Dare berbasis Wordwall, sedangkan kelompok kontrol tetap menggunakan metode konvensional. Hasil penelitian menunjukkan adanya peningkatan signifikan pada kepercayaan diri murid pada kelompok eksperimen. Peningkatan ini dapat dilihat dari murid yang lebih aktif, berani berpendapat, dan terlibat dalam diskusi kelas. Dengan demikian, media digital interaktif seperti Wordwall dapat menjadi alternatif strategi pembelajaran inovatif yang mendukung suasana belajar menyenangkan. Kata Kunci: pendidikan Pancasila dan kewarganegaraan; sikap percaya diri; truth or dare; wordwall